The Impact of Particulate Matter Air Pollution on Coronary Heart Disease: A Systematic Review - Gabriela Valencia Putri Husodho; Muhammad Abi Ghoffari Siregar; Agyta Hanifa Faiza (Diponegoro International Medical Journal, 2025)
Background: Coronary heart disease remains a significant global public health threat, with around 315 million patients in 2022, having risen due to global population growth, with regional disparities persisting. Air pollution, specifically fine particulate matter (PM) categorized according to size into PM2.5 and PM10, has been identified as a critical and modifiable determinant of coronary heart disease, associated with 4.2 million deaths globally in 2019, most of cardiovascular origin. Hence, a systematic review was conducted to assess the impact that PM2.5 and PM10 have on coronary heart disease. Coronary heart disease remains a significant global public health threat, with around 315 million patients in 2022, having risen due to global population growth, with regional disparities persisting. Air pollution, specifically fine particulate matter (PM) categorized according to size into PM2.5 and PM10, has been identified as a critical and modifiable determinant of coronary heart disease, associated with 4.2 million deaths globally in 2019, most of cardiovascular origin.Objective: To assess the impact that PM2.5 and PM10 have on coronary heart disease.Methods: A literature search was done to identify relevant articles using three databases (PubMed, ScienceDirect, EBSCO) between 2020-2025. Studies written in English and observational studies were included. Articles without complete data and case reports were excluded. The systematic review followed PRISMA guidelines.Results: 46 studies were included in the final synthesis. 24 studies discussed only PM2.5, 22 studies discussed both PM2.5 and PM10, while none of the studies discussed only PM10. The majority of the studies were conducted in China (21 studies). Overall, PM2.5 had higher OR, RR, and HR for coronary heart disease compared to PM10, due to its smaller size. Lower quality of life, which includes higher mortality and hospitalization rates, was also seen with higher PM exposure.Conclusion: PM exposure increases the risk of coronary heart disease occurrence and decreases quality of life in patients, with PM2.5 having a higher effect than PM10.